Polarization-entangled photon-pair source with van der Waals 3R-WS2 crystal - Feng, Jiangang (2024)
Ultracompact entangled photon sources are pivotal to miniaturized quantum photonic devices. Van der Waals (vdW) nonlinear crystals promise efficient photon-pair generation and on-chip monolithic integration with nanophotonic circuitry. However, it remains challenging to generate maximally entangled Bell states of photon pairs with high purity, generation rate, and fidelity required for practical applications. Here, we realize a polarization-entangled photon-pair source based on spontaneous parametric down conversion in an ultrathin rhombohedral tungsten disulfide (3R-WS2) crystal. This vdW entangled photonic source exhibits a high photon-pair purity with a coincidence-to-accidental ratio of above 800, a generation rate of 31 Hz, and two maximally polarization-entangled Bell states with fidelities exceeding 0.93 and entanglement degree over 0.97. These results stem from scalable optical nonlinearity, enhanced second-order susceptibility by electronic transitions, and a well-defined symmetry-enabled selection rule inherent in 3R-WS2. Our polarization entangled photon source can be integrated with photonic structures for generating more complex entangled states, thus paving an avenue for advanced quantum photonic systems toward computation and metrology.